Determinants Of Indonesian Coal Exports Volume: Autoregressive Distributed Lag (Ardl) Approach - Ego Bagas Anugerah Pratama; Dini Hariyanti; Sri Yani Kusumastuti (Cita Konsultindo Research Center, 2022)
The objective of this research was to analyze the short and long-term effect of Indonesia coal production levels, Coal Reference Prices (HBA), real exchange rates, China’s Manufacturing Purchasing Managers Index (PMI), Indonesia’s Manufacturing PMI, prices of biofuels (BBN) on Indonesia's coal export volume in the period of 2015 to 2021. This research used the Multiple Regression Method with the Autoregressive Distributed Lag (ARDL) model. The data used was monthly time series data for the period of August 2015 to August 2021. In the short term (1) the variable of coal production level has a significant positive effect on the volume of coal exports. (2) the real exchange rate variable has a significant negative effect on the coal exports volume. (3) the Indonesian manufacturing PMI variable has no significant effect on the coal exports volume. Whereas in the long term it showed that (1) the coal production level has a significant positive effect on the coal exports volume (2) the reference coal price has a significant positive effect on the coal exports volume. (3) The real exchange rate variable, the Indonesian manufacturing PMI, the Chinese Manufacturing PMI, and the price of biofuel have no significant effect on the Indonesian coal exports volume.